(3GdSQ GdeUhf aj Yde Gdecfhfs - (3YHO GdeLjO GdeUQjs
(3ChdgG (B:s
(3bGd ai GdebOeI GdeSeGg HbQGH GdhUhd ai eYQaI GdCUd (B: (3GYde Cf eHfi gPg GdUfGYI JJhba Ydi JWgjQ GdWHGFY GdCQHY s
(3BNQgG (B:s
(3hgPg fUjMI dc hdENhGfi GdeDefjf hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi eMeO hBdg hUMHg hSde JSdjeG cKjQkG CHOkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B290 - (3U(B295s
(3GdehLhO efJNHGJ efgs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B1033 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B65 s
Keywords: (3GdcjejGA h GdWHjYjGJs